Greenhouse Evaluation of Clubroot Resistant-Brassica napus cv. Mendel and Its Efficacy Concerning Virulence and Soil Inoculum Levels of Plasmodiophora brassicae - Nazanin Zamani-Noor; Imke Krohne; Birger Koopmann (Pathogens, 2021)
Clubroot resistance of oilseed rape (OSR) cultivars frequently relies on a major resistance gene originating from cv. Mendel. The efficacy of this resistance was studied in greenhouse experiments using two Plasmodiophora brassicae isolates, which were either virulent (P1(+)) or avirulent (P1) on Mendel. Seeds of clubroot-susceptible cultivar Visby and clubroot-resistant cultivar Mendel were sown in soil mixtures inoculated with different concentrations of resting spores (101, 103, 105, and 107 resting spores/g soil). Clubroot severity, plant height, shoot and root weight as well as resting spore propagation were assessed for each isolate and cultivar separately at four dates after sowing. The OSR cultivars behaved significantly different in the measured parameters. The threshold of inoculum density to cause disease depended strongly on the virulence of the pathogen and susceptibility of the host plant. In Visby grown in soil infested with P1, clubroot symptoms and increases in root weight and the number of propagated resting spores occurred at inoculum levels of 101 resting spores and higher, whereas Mendel was not affected in soils under the three lowest inoculum densities. In contrast, the P1(+) isolate led to earlier and more severe symptoms, heavier galls, and a significantly higher number of new resting spores in both cultivars.